Lung function and associations with multiple dimensions of dental health: a prospective observational cross-sectional study. (December 2016) - Henke, Christian; Budweiser, Stephan; Jörres, Rudolf
Abstract Background Epidemiological data suggest an association between respiratory diseases and periodontal health. However, the link between the overall dental status and single lung function measures, within a practical clinical context, is not well studied. Methods Following a prospective cross-sectional design, consecutive adult patients were evaluated. Next to spirometry, anthropometric data, profession, smoking status, symptoms, self-rated exercise performance, comorbidities, allergies and medication were determined. Assessment of dental status comprised carious lesions, dental fillings, missing teeth, dentures, insufficient fillings/dentures, implants, oral mucosa diseases, calculus, decayed-missed-filling-teeth (DMF-T)-index, periodontal screening-index, and orthopantomograms. Results Among 587 adult patients considered, 206 were included (119 female; median age 42.0 years; 56 % smoking history). Most patients had dental fillings (86.9 %), fix/mobile dentures (66.5 %), missing teeth (56.8 %) and calculus (84.0 %), the overall DMF-T being 15 (9; 21). Periodontitis was present in 53.9 %, an abnormal orthopanthomogram in 47.9 % of subjects. Regarding spirometric indices expressed as % predicted, dentures, missing teeth, oral mucosal diseases and a DMF-T > 15 (median) were associated with lower maximal expiratory flows at 25 % of vital capacity (MEF25 ) (p < 0.05 each). In adjusted logistic regression analyses, only dentures were associated with low MEF25 % predicted and with the ratio of forced expiratory volume in 1 s to forced vital capacity (FEV1 /FVC; p < 0.05 each). However, periodontitis and DMF-T were linked to age (p < 0.001) and packyears (p < 0.05) only. Conclusion Within a real-life clinical setting, only the presence of dentures showed weak associations with lung function, suggesting small airways dysfunction and obstruction. Most of the associations were explained by smoking habits and age.